The relationship between emotional intelligence and negative mental states of students - Irina A. Solovyova; Svetlana A. Solovyova; Natalia Y. Evsyukova (Развитие образования)
The period of study at a higher education institution is accompanied by significant cognitive and emotional stresses associated with academic requirements, social adaptation and professional self-determination. These factors create prerequisites for the occurrence of stressful situations and the intensification of negative mental states such as anxiety, frustration, aggressiveness and rigidity. Under conditions of chronic stress, these conditions can develop into maladaptive behaviors, reducing academic motivation and worsening students' overall mental health. The article examines the relationship between the level of emotional intelligence, previously differentiated on the basis of the analysis into three groups (high, medium and low levels), and the severity of negative mental states, including situational and personal anxiety, frustration, aggressiveness and rigidity, which made it possible to identify the features of their mutual influence in the student sample. The data allow us to conclude that the level of emotional intelligence has a moderating effect on the intensity of experiencing negative mental states among students, where a high level of emotional intelligence contributes to a decrease in the severity of all negative states studied, while a low level of emotional intelligence is associated with their intensification. It is concluded that it is necessary to include emotional intelligence development programs in the educational process in order to increase the psychological stability of students and their adaptation to learning conditions.